Biodegradability of Metal Alloys: in vivo Testing - J. Levorová; J. Dušková; M. Drahoš; R. Vrbová; J. Kubásek; D. Vojtěch; M. Bartoš; L. Dugová; D. Ulmann; R. Foltán (Czech Dental Chamber, 2017)
Introduction and aim: The standard material used for osteosynthesis of the facial skeleton is the titan and its compounds. One of the disadvantages of the conventional material is the need for its extraction in indicated cases. Degradable material offer a solution to the situation. In the past, materials based on polylactic or polyglycolic acid were used for these purposes. It clinically proved to be unsatisfactory. The modern solution is the use of biodegradable metal alloys. The authors present original research on the degradation of metal materials based on magnesium and zinc on the biomodels. Materials and methods: A total of 12 animal models (rabbits) were used. Screws of 3 types of metals (Zn-2Mg and WE43 degradable alloys and the titanium as a standard material) were implanted in the rabbit's tibias. The animals were euthanasied in 4-weeks intervals, samples of bone tissue with an implanted material have been scaned under mikrofocus CT and were histologically examined. The rate of degradation of the materials was examined. Results: Time period of degradation of the material WE43 under physiological conditions has been shown to be too short to stabilize the fracture. Material of Zn-2 mg during the 16 weeks showed a minimum ability to degradation. Both materials have demonstrated reasonable biological properties. Conclusion: Degradable materials based on magnesium and zinc are from the biological point of view matching materials. The results of this research indicates that the use of both types of alloys does not satisfy the materials requirments, i.e. retained strength for 12-24 weeks and degradation in reasonable time frame..